Costs and impact on HIV transmission of a switch from a criminalisation to a public health approach to injecting drug use in eastern Europe and central Asia: a modelling analysis. Issue 1 (January 2022) - Ward, Zoe; Stone, Jack; Bishop, Chrissy; Ivakin, Viktor; Eritsyan, Ksenia; Deryabina, Anna; Low, Andrea; Cepeda, Javier; Kelly, Sherrie L; Heimer, Robert; Cook, Robert; Altice, Frederick L; et al.
Summary: Background: HIV incidence is increasing in eastern Europe and central Asia, primarily driven by injecting drug use. Coverage of antiretroviral therapy (ART) and opioid agonist therapy are suboptimal, with many people who inject drugs (PWID) being incarcerated. We aimed to assess whether use of monies saved as a result of decriminalisation of drug use or possession to scale up ART and opioid agonist therapy could control HIV transmission among PWID in eastern Europe and central Asia. Methods: A dynamic HIV transmission model among PWID incorporating incarceration, ART, and opioid agonist therapy was calibrated to Belarus, Kazakhstan, Kyrgyzstan, and St Petersburg (Russia). Country-specific costs for opioid agonist therapy, ART, and incarceration were collated or estimated. Compared with baseline, the model prospectively projected the life-years gained, incremental costs (2018 euros), and infections prevented over 2020–40 for three scenarios. The decriminalisation scenario removed incarceration resulting from drug use or possession for personal use, reducing incarceration among PWID by 24·8% in Belarus, Kazakhstan, and Kyrgyzstan and 46·4% in St Petersburg; the public health approach scenario used savings from decriminalisation to scale up ART and opioid agonist therapy; and the full scale-up scenario included the decriminalisation scenario plus investment of additional resources to scale up ART to the UNAIDS 90-90-90 target of 81% coverage and opioid agonist therapy to the WHO target of 40% coverage. The incremental cost-effectiveness ratios per life-year gained for each scenario were calculated and compared with country-specific gross domestic product per-capita willingness-to-pay thresholds. Costs and life-years gained were discounted 3% annually. Findings: Current levels of incarceration, opioid agonist therapy, and ART were estimated to cost from €198 million (95% credibility interval 173–224) in Kyrgyzstan to €4129 million (3897–4358) in Kazakhstan over 2020–40; 74·8–95·8% of these total costs were incarceration costs. Decriminalisation resulted in cost savings (€38–773 million due to reduced prison costs; 16·9–26·1% reduction in overall costs) but modest life-years gained (745–1694). The public health approach was cost saving, allowing each setting to reach 81% ART coverage and 29·7–41·8% coverage of opioid agonist therapy, resulting in 17 768–148 464 life-years gained and 58·9–83·7% of infections prevented. Results were similar for the full scale-up scenario. Interpretation: Cost savings from decriminalisation of drug use could greatly reduce HIV transmission through increased coverage of opioid agonist therapy and ART among PWID in eastern Europe and central Asia. Funding: Alliance for Public Health, US National Institute of Allergy and Infectious Diseases and National Institute for Drug Abuse, and Economist Intelligence Unit.